ANALISIS PENGELOLAAN PAJAK BUMI DAN BANGUNAN PERDESAAN DAN PERKOTAAN (PBB-P2) - Nasution, Rakhma Idawani; Heriyanto, Meyzi; Farida, Lena (Jurnal Ilmu Administrasi Negara, 2018)
Analysis of Land and Rural Land and Urban Tax Management (PBB-P2). This study aims to determine how the readiness of the Government of Meranti Islands in the management of Land and Rural Land and Urban Tax (PBB P2) as a local tax. Respondents in this study amounted to 47 people consisting of employees of Dinas DPPKAD Kabupaten Kepulauan Meranti. The type of research is quantitative descriptive. Data collection techniques are questionnaires and interviews. The data were analyzed using Likert scale. Based on data analysis using Regulation indicator, Human Resources, Facilities and infrastructure, Budget, Socialization, and Cooperation with related parties it can be concluded that the Local Government of Meranti Islands Regency is Ready to implement the Application of Law Number 28 Year 2009 on Tax Regional and Retribution.